BS EN IEC 61300-3-35. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 3-35. Examinations and measurements. Visual inspection of fibre optic connectors and fibre-stub transceivers (10th January 2020) - British Standards Institution,
No abstract available